Threatened or Data Deficient: assessing the conservation status of poorly known species. Issue 5 (12th January 2016) - Roberts, David L.; Taylor, Lin; Joppa, Lucas N.
Abstract: Aim: To determine whether extinction risk assessments based on biological collections and using Criterion B of the IUCN Red List Criteria reflect in part an accurate measure of species rarity and thus extinction risk. Location: Madagascar. Methods: We calculate the extent of occurrence (EOO) and area of occupancy (AOO) for orchids using herbarium specimen data. Correlations were made against range, occupancy, extinction risk, number of specimens and the date of description. We calculated the average increase in range per species specimen, correlated this against the date of description and determined significance of the observed EOO accumulation using randomization tests. Results: Significant negative correlations were found between date of description and all measures of range, occupancy and associated Red List Categories and number of specimens, as well as between the average range accumulation per specimen and date of description. Seventy‐five percentage of species' observed EOO accumulations significantly differed from random. Maximum deviations between observed EOO accumulations and those derived from random sampling were always significantly positive. For most species, this occurred more frequently during the first half of the accumulation sequence. Main conclusions: Species described more recently have smaller ranges and occupancies, fewer specimens and greater perceived extinction risk status. Levels of geographic uniqueness of collections are higher in species described more recently. Awareness of a species range increased faster than random, particularly in the first half of the sampling process, suggesting that newly discovered or yet to be discovered species are rare and likely have a higher risk of extinction. For many species, biological collections represent the sum of our knowledge. While data may be limited, such species should be listed in an appropriate Red List Category in accordance with the IUCN Red List Guidelines rather than as Data Deficient.